2002
DOI: 10.1117/12.455133
|View full text |Cite
|
Sign up to set email alerts
|

<title>Use of remote sensing to determine plant health and productivity</title>

Abstract: This project seeks to assess plant productivity and health in time and space by measuring spectral reflectance from soybean canopies using remote sensing images that do not require ground assessment. Aerial images and reflectance measurements from a multi-spectral radiometer were obtained simultaneously from a soybean field located in Story County, Iowa. The multi-spectral radiometer has eight wavelength bands, ranging from 460-nm to 810-nm and was used as a ground reference for the data analysis. Aerial image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Gittelson et al (1996) found that substituting green band for red band in NDVI gives better estimation of green biomass because green band is more sensitive to the chlorophyll concentrations. Vegetative indices have been widely used to relate the reflectance of various major crops to ground leaf cover as related to in-season N fertilization requirements for corn (Ma et al 1996;Sripada et al 2005) and wheat (Mahey et al 1991;Stone et al 1996), early prediction of soybean yield (Ma et al 2001), crop nutrient deficiencies (Blackmer and Schepers 1996) and crop health (Hart and Myers 1968;Toler et al 1981;Chong et al 2002). Similarly Shawn and Kelley (2005) used color-infrared and NDVI images as a scouting tool for soybean crop anomalies such as IDC, herbicide damage, and patches of weeds.…”
Section: Introductionmentioning
confidence: 99%
“…Gittelson et al (1996) found that substituting green band for red band in NDVI gives better estimation of green biomass because green band is more sensitive to the chlorophyll concentrations. Vegetative indices have been widely used to relate the reflectance of various major crops to ground leaf cover as related to in-season N fertilization requirements for corn (Ma et al 1996;Sripada et al 2005) and wheat (Mahey et al 1991;Stone et al 1996), early prediction of soybean yield (Ma et al 2001), crop nutrient deficiencies (Blackmer and Schepers 1996) and crop health (Hart and Myers 1968;Toler et al 1981;Chong et al 2002). Similarly Shawn and Kelley (2005) used color-infrared and NDVI images as a scouting tool for soybean crop anomalies such as IDC, herbicide damage, and patches of weeds.…”
Section: Introductionmentioning
confidence: 99%
“…Plant analyses are mainly focused on the chlorophyll content [25] or substances contained in plants [91] and, consequently, the condition of plants [24,27]. Research on the growth and development of vegetation can be carried out in both strictly controlled laboratory conditions [29,79,92,93] and using satellite techniques [42,44,46,[49][50][51]56,59,61,62,[64][65][66]68,71,[75][76][77][78]80,88, or other means of transporting remote sensing devices (UAV, airships, airplanes) [43,47,54,55,65,84,[108][109][110]118,[140][141][142][143][144][145][146][147][148]…”
Section: Introductionmentioning
confidence: 99%